ANALISA DAN PERANCANGAN SISTEM INFORMASI PRAKTEK KERJA LAPANGAN (PKL) BERBASIS WEB (STUDI KASUS : SMK NEGERI 4 BATANG HARI ) - Lisdarti, Lisdarti; Hardianti, Siti (LP2M Universitas Nurdin Hamzah, 2023)
Information systems are one of the most important needs of society in the current era of globalization. One important aspect that is needed especially in the field of education is school. With the application of information systems in schools can also help the school produce information that is accurate, timely and relevant. At SMK Negeri 4 Batanghari there is an activity called Field Work Practice (PKL). In this street vendor activity, the SMK Negeri 4 Batanghari school still uses a manual system in registering students which results in the performance of the school being less effective. The implementation of the street vendor system aims to build a system that can facilitate the management and reporting of street vendors by students and street vendor managers at SMK Negeri 4 Batanghari. This research was conducted using a responsive web. By using the PHP programming language and MySQL database where the authors carry out system development with design analysis, system design, UML (Unified Modeling Language), that is, can provide a visual or image modeling language to users of various kinds of programming and general engineering processes. Bringing together the best available information in modeling, table design and interface design. This system displays class data, department data, year data, supervisor data, supervisor data, student guardian data, student data, and reports that can be printed with the aim of being able to provide fast and easy information in conducting Job Training Applications (PKL). Responsive Web Based.